A comparative study of closure versus non-closure of hernial defect in laparoscopic ventral hernia mesh repair - M., Nandeesh; M. V., Akash (International Surgery Journal, 2019)
Background: Laparoscopic ventral hernia repair has better out comes when compared to open mesh repair. But closure of the hernial defect is still a contentious issue. This study is designed to compare the outcome of closure versus non-closure of hernia defect in laparoscopic ventral hernia repair. Methods: A 2 years prospective randomized controlled study was conducted on 60 patients undergoing elective laparoscopic ventral hernia repair in the Department of General Surgery (November 2016 to October 2018). Results: The patients in the two groups were analyzed using Chi-square, ANOVA, Fisher exact test, and results were formulated. The mean age of ventral hernia was 41 years and overall incidence more in females. Paraumbilical hernia is the commonest variety of ventral hernia and 63.3% hernias were reducible. Average post-operative length of hospital stay was 2 days with no difference in both the groups. Post-operative pain was more in intraperitoneal onlay mesh (IPOM) plus group. Seroma formation and Incidence of mesh bulge was found be more in IPOM group, but there was no difference in the incidence of chronic pain or recurrence rate between the two groups. All the above proved statistical significance. Conclusions: Primary defect closure in ventral hernia along with mesh placement in laparoscopy seems to have better outcome, with respect to less chance of seroma formation and mesh bulge.